Reconfiguration of sediment fungal communities following coastal aquaculture pond restoration: coupling diversity shifts, assembly mechanisms and network stability - Chengfeng Yu; Ziyi Zhou; Jingjing Li; Huan Zhang; Min Xu (Marine Environmental Research, 2026)

Strain-dependent metabolic remodelling by indigenous yeasts from fermented sausages enhances saltiness responses in a low-NaCl meat slurry model - Han Li; Yuan Li; Yiwen Zhao; Mengqi Wu; Qianqian Yu; Chengfeng Sun; Zhenjun Zhao; Rongxin Wen (Food Research International, 2026)

Long-term low-salt and high-salt diets differentially disrupt the gut–metabolite–brain axis and induce cognitive impairment - Anji Chen; Shilong Hu; Fansen Zeng; Chengfeng Yu; Danying Chen; Xingqian Ye; Zengliang Jiang; Shiguo Chen (Food Research International, 2026)

Fermentation-driven dynamic formation of salty peptides and mechanisms of saltiness enhancement in sausage - Chuanjun Xu; Mengqi Wu; Ai-jia Liu; Yuan Li; Yiwen Zhao; Chengfeng Sun; Qianqian Yu; Rongxin Wen (Food Research International, 2026)

Multi-dimensional analyses unveil strain-specific metabolic perturbations and flavour deterioration traits induced by spoilage bacteria in cold-stored chicken breast - Chuanjun Xu; Jing Yi; Ai-jia Liu; Yiwen Zhao; Mengqi Wu; Yuan Li; Qianqian Yu; Chengfeng Sun; Rongxin Wen (International Journal of Food Microbiology, 2026)

Restoration of aquaculture ponds to coastal wetlands enhances bacterial resilience by reshaping community structure and interaction networks - Chengfeng Yu; Shengzhi Liu; Ziyi Zhou; Jingjing Li; Huan Zhang; Min Xu (Aquaculture, 2026)

Direct functional recycling of waste polyester-cotton blended textiles into photothermal materials for solar-driven water evaporation and anti-icing/de-icing - Zijun Feng; Lan Bai; Jing Yu; Wenhao Xu; Chengfeng Shen; Yifan Liu; Yiling Wu; Shimei Xu; Yuzhong Wang (Chemical Engineering Journal, 2026)

Unraveling flavor evolution in beef: the impact of aging methods and duration on precursors and volatile compounds - Silu Ze; Qianqian Liu; Xiangku Ye; Rongxin Wen; Chengfeng Sun; Qianqian Yu (Food Chemistry, 2026)

Integrating hyperspectral imaging to reveal freeze-thaw induced quality and myofibrillar functional deterioration in chicken meat - Yuqing Liu; Xiaojie Yu; Rongxin Wen; Fei Chen; Zunwu Zhou; Chengfeng Sun; Qianqian Yu (Food Research International, 2026)

Bioturbation experiment reveals the negative impact of physical damage and shading on the growth of Vallisneria spinulosa S. Z. Yan, a rapidly declining submerged macrophyte in the lower Yangtze region - Min Guo; Zhe Li; Chengfeng Luo; Shaoxia Xia; Yunzhe Huang; Geng Huang; Chenglin Li; Leiqiang Gong; Zonghua Zhang; Yong Mei; Hao Luo; Xiubo Yu; et al. (Hydrobiologia, 2026)

Exploring the potential ecological risks of cadmium accumulation in coastal sediments: implications for diversity, function, and assembly of fungal community - Chengfeng Yu; Wen Du; Kun Meng; Xiang Chen; Huan Zhang; Min Xu (Journal of Environmental Management, 2025)

Recent advances of nano zero-valent iron (nZVI) on the remediation of heavy metals polluted environment: Modified methods, mechanisms, influencing factors and application challenges - Yihui Zhang; Huan Zeng; Yuan Yuan; Chengfeng Jiang; Wantong Xie; Ying Zheng; Yu Peng (Journal of Environmental Chemical Engineering, 2025)

Multiscale analysis of ultrasound-induced microstructural remodelling governing salt diffusion and quality attributes in chicken breast - Hongyu Li; Fei Chen; Qianqian Yu; Chengfeng Sun; Rongxin Wen (Innovative Food Science & Emerging Technologies, 2025)

Modulation of flavour perception under sodium-reduced conditions: A sensory–metabolic interaction framework driven by Debaryomyces hansenii SH4 and KCl - Han Li; Hongyu Li; Qianqian Yu; Chengfeng Sun; Huaishu Wang; Yonglin Gao; Rongxin Wen (Food Research International, 2025)

Decoding spoilage metabolism in chicken breast: a functional microbial perspective on off-flavor formation - Jing Yi; Fei Chen; Chuanjun Xu; Xinlu Yan; Yifan Wang; Qianqian Yu; Chengfeng Sun; Rongxin Wen (International Journal of Food Microbiology, 2025)

Impact of wooden breast myopathy on meat quality and myofibrillar protein functionality in chicken - Xiaojie Yu; Fei Chen; Ting Tang; Chengfeng Sun; Rongxin Wen; Qianqian Yu (Food Chemistry, 2025)

Structural and functional modifications of Porphyra yezoensis proteins via ultrasound-assisted enzymolysis: insights into taste enhancement and mechanisms - Rongxin Wen; Xinlu Yan; Fanxue Kong; Fei Chen; Yang Zang; Chengfeng Sun; Qianqian Yu (Food Chemistry, 2025)

Lipidomics-based insights into the mechanism of muscle-specific quality differences during wet-aging - Ting Tang; Chengfeng Sun; Rongxin Wen; Zhenjun Zhao; Qianqian Yu (Food Chemistry, 2025)

Oxidative–textural coupling mechanisms in chicken breast stored at low-temperature gradients: Super-chilling as a quality preserving strategy - Jing Yi; Fei Chen; Han Li; Qianqian Yu; Chengfeng Sun; Rongxin Wen (Food Research International, 2025)

Nanocellulose composites with enhanced mechanical and flame-retardant properties based on grafting of inorganic organic/multilayer core-shell matter — MSNs-TMSB/DA/TOCNF - Qingshuo Wang; Lanfeng Hui; Yiyi Zhang; Wenwen Guo; Chengfeng Zhu; Mingyue Zhao; Qian Yang; Yu Qu; Zitong Zhang (Carbohydrate Polymers, 2025)

Study on the lateral breakout resistance of submarine pipelines in the sand wave area - Run Liu; Yinze Guan; Chengfeng Li; Xiang Sun; Yinuo Liu; Zheng Yu (Ocean Engineering, 2025)

Metabolic and sensory profiling of edible seaweeds: Unraveling the biochemical basis of taste profile complexity - Xinlu Yan; Fei Chen; Qingqing Liu; Chengfeng Sun; Qianqian Yu; Rongxin Wen (Food Research International, 2025)

Electrospun PLA/ZnO composite films: Enhanced antibacterial properties and application in fresh chicken meat preservation - Dengao Li; Fei Chen; Zhaojing Dong; Fei Jia; Rongxin Wen; Chengfeng Sun; Qianqian Yu (Food Packaging and Shelf Life, 2025)

Comprehensive analyses of meat quality and metabolome alterations with aging under different aging methods in beef - Qianqian Liu; Xiaojie Yu; Fei Jia; Rongxin Wen; Chengfeng Sun; Qianqian Yu (Food Chemistry, 2025)

Centrifuge model study of vertical ultimate bearing capacity of pile foundations in overconsolidated clay - Run Liu; Yu Jiang; Chengfeng Li; Guangsi Chen; Chunyang Su; Xiaoyu Long (Ocean Engineering, 2025)

Unravelling the effects of drying techniques on Porphyra yezoensis: Morphology, rehydration properties, metabolomic profile, and taste formation - Xinlu Yan; Hongyu Li; Jing Yi; Chengfeng Sun; Qianqian Yu; Rongxin Wen (Food Chemistry, 2025)

Protective effects of polyphenol-rich sugarcane molasses extract against AGEs-induced glycosylation damage in L929 cells - Min Wang; Junru Wang; Wenhui Li; Chengfeng Zhang; Yu Xi; Yanv Zhou; Xinqi Liu; He Li (Food Bioscience, 2025)

Extracting waterline and inverting tidal flats topography based on Sentinel-2 remote sensing images: A case study of the northern part of the North Jiangsu radial sand ridges - Jicheng Cao; Qing Liu; Chengfeng Yu; Zhou Chen; Xinrui Dong; Min Xu; Yifei Zhao (Geomorphology, 2024)

Study on the motion patterns of shallow-embedded pipelines in sand - Run Liu; Zheng Yu; Chengfeng Li; Xintong Hao (Marine Georesources & Geotechnology, 2024)

Impacts of cadmium accumulation on the diversity, assembly processes, and co-occurrence patterns of archaeal communities in marine sediments - Chengfeng Yu; Kun Meng; Zhiyong Zhu; Shengzhi Liu; Ziyi Zhou; Huan Zhang; Min Xu (Science of The Total Environment, 2024)

Optimization of ultrasonic extraction of bioactive components from Alpiniae oxyphyllae Fructus using response surface methodology - Yuyi Liu; Ruimin Wang; Xuan Hu; Chengfeng Yu; Zexin Wang; Lin Zhang; Sixin Liu; Congfa Li (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Effect of wet-aging on meat quality and exudate metabolome changes in different beef muscles - Qianqian Yu; Xuejing Gu; Qianqian Liu; Rongxin Wen; Chengfeng Sun (Food Research International, 2024)

Study on the dynamic embedment variation of shallow embedded submarine pipelines in sand - Zheng Yu; Run Liu; Chengfeng Li; Xintong Hao (Ocean Engineering, 2023)

Theoretical and Numerical Studies on the Coupling Deformation of Global Lateral Buckling and Walking of Submarine Pipeline - Run Liu; Xintong Hao; Chengfeng Li; Qingxin Li; Zheng Yu; Dang Zhao (Journal of Ocean University of China, 2023)

Unveiling the impact and mechanisms of Cd-driven ecological assembly and coexistence of bacterial communities in coastal sediments of Yellow Sea - Chengfeng Yu; Zhiyong Zhu; Kun Meng; Huan Zhang; Min Xu (Journal of Hazardous Materials, 2023)

Coexistence of Tree Species Promotes the Similarity of the Elementome in Soil Profiles - Xiaochang Wu; Huayong Zhang; Tousheng Huang; Chengfeng Yu; Shijia Zhang; Yonglan Tian (Journal of Soil Science and Plant Nutrition, 2023)

Dynamics of soil net nitrogen mineralization and controlled effect of microbial functional genes in the restoration of cold temperate forests - Xiumin Zhang; Huayong Zhang; Tousheng Huang; Chengfeng Yu; Yu Feng; Yonglan Tian (Applied Soil Ecology, 2023)

Acetobacter sp. improves the undesirable odors of fermented noni (Morinda citrifolia L.) juice - Lin Zhang; Qiongping Hong; Chengfeng Yu; Ruimin Wang; Congfa Li; Sixin Liu (Food Chemistry, 2023)

A Novel Mutation in COL4A1 Gene in a Chinese Family with Pontine Autosomal Dominant Microangiopathy and Leukoencephalopathy - Qing Li; Chengfeng Wang; Wei Li; Zaiqiang Zhang; Shanshan Wang; Autongsha Wupuer; Xiao Hu; Kalibinuer Wumaier; Yi Zhu; Hongyan Li; Wengui Yu (Translational Stroke Research, 2022)
Pontine autosomal dominant microangiopathy and leukoencephalopathy (PADMAL) is a rare hereditary cerebral small vessel disease. We report a novel collagen type IV alpha 1 ( COL4A1 ) gene mutation in a Chinese family with PADMAL. The index case was followed up for 6 years. Neuroimaging, whole-exome sequencing, skin biopsy, and pedigree analysis were performed. She initially presented with minor head injury at age 38. MRI brain showed chronic lacunar infarcts in the pons, left thalamus, and right centrum semiovale. Extensive workup was unremarkable except for a patent foramen ovale (PFO). Despite anticoagulation, PFO closure, and antiplatelet therapy, the patient had recurrent lacunar infarcts in the pons and deep white matter, as well as subcortical microhemorrhages. Whole-exome sequencing demonstrated a novel c.*34G > T mutation in the 3′ untranslated region of COL4A1 gene. Skin biopsy subsequently demonstrated thickening of vascular basement membrane, proliferation of endothelial cells, and stenosis of vascular lumen. Three additional family members had gene testing and 2 of them were found to have the same heterozygous mutation. Of the 18 individuals in the pedigree of 3 generations, 12 had clinical and MRI evidence of PADMAL. The mechanisms of both ischemic and hemorrhagic stroke are likely the overexpression of COLT4A1 in the basement membrane and frugality of the vessel walls. Our findings suggest that the novel c.*34G > T mutation appears to have the same functional consequences as the previously reported COL4A1 gene mutations in patients with PADMAL and multi-infarct dementia of Swedish type.

AUV Obstacle Avoidance Planning Based on Deep Reinforcement Learning - Jianya Yuan; Hongjian Wang; Honghan Zhang; Changjian Lin; Dan Yu; Chengfeng Li (Journal of Marine Science and Engineering, 2021)
In a complex underwater environment, finding a viable, collision-free path for an autonomous underwater vehicle (AUV) is a challenging task. The purpose of this paper is to establish a safe, real-time, and robust method of collision avoidance that improves the autonomy of AUVs. We propose a method based on active sonar, which utilizes a deep reinforcement learning algorithm to learn the processed sonar information to navigate the AUV in an uncertain environment. We compare the performance of double deep Q-network algorithms with that of a genetic algorithm and deep learning. We propose a line-of-sight guidance method to mitigate abrupt changes in the yaw direction and smooth the heading changes when the AUV switches trajectory. The different experimental results show that the double deep Q-network algorithms ensure excellent collision avoidance performance. The effectiveness of the algorithm proposed in this paper was verified in three environments: random static, mixed static, and complex dynamic. The results show that the proposed algorithm has significant advantages over other algorithms in terms of success rate, collision avoidance performance, and generalization ability. The double deep Q-network algorithm proposed in this paper is superior to the genetic algorithm and deep learning in terms of the running time, total path, performance in avoiding collisions with moving obstacles, and planning time for each step. After the algorithm is trained in a simulated environment, it can still perform online learning according to the information of the environment after deployment and adjust the weight of the network in real-time. These results demonstrate that the proposed approach has significant potential for practical applications.

Phylogenetic and genetic characterization of a 2017 clinical isolate of H7N9 virus in Guangzhou, China during the fifth epidemic wave - Yongqiang Deng; Chunlin Li; Jianfeng Han; Yingfen Wen; Jian Wang; Wenxing Hong; Xiaofeng Li; Zhongyu Liu; Qing Ye; Jing Li; Changshuai Zhou; Lei Yu; et al. (Science China Life Sciences, 2017)

Identification of novel ATP7A mutations and prenatal diagnosis in Chinese patients with Menkes disease - Binbin Cao; Xiaoping Yang; Yinyin Chen; Qionghui Huang; Ye Wu; Qiang Gu; Jiangxi Xiao; Huixia Yang; Hong Pan; Junya Chen; Yu Sun; Li Ren; et al. (Metabolic Brain Disease, 2017)

Isolation and characterization of dengue virus serotype 2 from the large dengue outbreak in Guangdong, China in 2014 - Hui Zhao; LingZhai Zhao; Tao Jiang; XiaoFeng Li; Hang Fan; WenXin Hong; Yu Zhang; Qin Zhu; Qing Ye; YiGang Tong; WuChun Cao; FuChun Zhang; et al. (Science China Life Sciences, 2014)

Influence of hydrophilic amino acids and GC-content on expression of recombinant proteins used in vaccines against foot-and-mouth disease virus in Escherichia coli - Hongfei Wei; Mingli Fang; Min Wan; Hua Wang; Peiyin Zhang; Xiaoping Hu; XiuLi Wu; Ming Yang; Yongsheng Zhang; Lei Zhou; Chengfeng Jiao; Li Hua; et al. (Biotechnology Letters, 2014)